cual es el resultado de (x-6)(x-6)
Respuestas a la pregunta
Contestado por
13
(x-6)(x-6)
(x - 6) ¹⁺¹
(x - 6)²
Respuesta :
(x - 6)²
(x - 6) ¹⁺¹
(x - 6)²
Respuesta :
(x - 6)²
Contestado por
21
Resolver.
(x - 6)(x - 6) =
(x - 6)² = Aplicas productos notables
(a + b)² = a² - 2ab + b²
x² - 2(x)(6) + 6² =
x² - 12x + 36
Respuesta.
x² - 12x + 36
(x - 6)(x - 6) =
(x - 6)² = Aplicas productos notables
(a + b)² = a² - 2ab + b²
x² - 2(x)(6) + 6² =
x² - 12x + 36
Respuesta.
x² - 12x + 36
Otras preguntas
Ciencias Sociales,
hace 8 meses
Religión,
hace 8 meses
Matemáticas,
hace 1 año
Física,
hace 1 año
Castellano,
hace 1 año
Geografía,
hace 1 año